A Historical Analysis of Maternal and Child Health Programs in 1980s South Korea: Insights from Maternal and Child Health Centers - Dahye JEONG (Uisahak)
This article examines the historical trajectory of South Korea’s maternal and child health (MCH) programs from the late 1970s to the 1980s, focusing on the establishment and operation of MCH centers funded by the World Bank population loan. It investigates how these centers reflected the evolving relationship between population control policies and public health services within South Korea's developing healthcare system.The MCH centers, established nationwide but primarily located in rural areas, were intended to improve maternal and infant health indicators while ultimately contributing to fertility reduction. Despite the ambitious vision of integrating family planning with comprehensive maternal and child healthcare, the centers faced significant challenges, including funding shortages, difficulties in recruiting midwives, and competition from the rapidly expanding private medical sector, which offered modern diagnostic technologies and access to specialist physicians. In response, the government attempted to redirect remaining funds toward establishing comprehensive MCH centers within private hospitals; however, this shift did not substantially increase the utilization of local MCH centers.This study demonstrates that, despite the rhetoric emphasizing maternal and child health, MCH programs remained subordinate to fertility control objectives within South Korea’s population policy framework. The history of these centers highlight the tension between demographic goals and public health service needs, as well as the complex interplay between international development organizations, national policy priorities, and local healthcare practices during a period of rapid social transformation in South Korea.